Evaluation Of Molecular Markers Associated With Significant Neonatal Hyperbilirubinemia Of The Three Ethnic Groups In Malaysia - Shwe, Sin (2020)
The aim of this study was to identify the major genetic risk factors associated with significant hyperbilirubinemia among Malaysian jaundiced newborn infants and also the prevalences of genetic variants of these four genes. Significant neonatal hyperbilirubinemia (SigNH) was defined as total serum bilirubin (TSB) leveled off at 17 mg/dL (≥291 µmol/L) in the term infants. In addition, this study determined the association between co-expression of two or more of genetic variants with significant hyperbilirubinemia in Malaysian newborn infants. This study identified the genetic variants of UDP-glucuronosyltransferase (UGT) 1A1, glucose-6-phosphate dehydrogenase (G6PD), solute carrier organic anion transporter family membrane 1B1 (SLCO1B1) and non-deletional alpha- iii thalassemia in Malaysia newborn infants with and without significant hyperbilirubinemia by using PCR-RFLP (Polymerase Chain Reaction- Restriction Fragment Length Polymorphism) method. Samples which were positive for the detection of mutations according to the above described methods were verified by DNA sequencing. This study recruited 1121 hyperbilirubinemic neonates. The study indicates that the percentage of significant neonatal hyperbilirubinemia was 62.1% (696 of 1121) in Malaysian neonates. Males had 51.2% (574 of 1121) and females showed 48.8% (547 of 1121) in this study. In addition, Malay had the highest percentage of hyperbilirubinemia (74.9%) while Indian had lowest number in our study population (3.2%). Malaysian Chinese and others showed 16.9% and 5.0% respectively. There were no significant differences in the gender and ethnic distribution between SigNH and non-SigNH in the study population. The result of the present study showed that 70.7% (793/1121) of the main ethnic groups of neonates carried a UGT1A1 gene mutation. This study detected UGT1A1 gene variants 211G>A (3.2%), 686C>A (1.1%), 1091C>T (0.4%), 1456T>G (1.3%), c.-3279T>G (76.2%) and promoter A(TA)nTAA (17.9%). The commonest mutations found were c.-3279T>G and TA repeat at promoter region. Moreover, genotypic and allelic distribution of variants UGT1A1 gene 211G>A and TA promoter region repeat were significantly associated in their frequencies with SigNH group showed OR: 6.26 (p = 0.02) and OR: 3.26 (p = 0.001). However, the iv c.-3279T>G variant mutation was significantly associated in the frequency with non-SigNH showed OR: 0.31 (p = 0.001). In addition, all randomly selected 300 samples of SigNH (n = 200) and non-SigNH (n = 100) showed homozygous 214G>C mutation in sequencing analysis. Out of total 1121 subjects studied, 3.1% (35/1121) were found to have G6PD mutation. This study detected variant mutations of G6PD nt 1388G>A (60.0%), nt 871G>A (17.1%), nt 487G>A (14.3%), nt 1376G>T (5.7%) and nt 1003G>A (2.9%). The predominant variation in the G6PD gene was nt 1388 G>A (G6PD Kaiping), followed by 871 G>A (G6PD Viangchan). None of the G6PD gene mutations showed significant difference in their frequencies in SigNH and non-SigNH groups. The present study did not find any mutations of nucleotide 563 C>T, 383T>C, and 131 C>G in our study population. In this study, 49.3% (553/1121) were found to have SLCO1B1 gene mutation. The study observed the variants c.388G>A mutation (53.3%) and c.521C>T mutation (46.7%). Logistic regression analysis of the variant 388G>A mutation showed significance risk for SigNH group (p = 0.05). There were two cases of heterozygous variation of non-deletional alphathalassemia Hb CS gene detected in SigNH group (0.2%), one Malaysian Malay and one Malaysian Chinese. No Hb Adana gene mutation was found either in SigNH or in non-SigNH cases. v A total of 357 coexpressed cases were found in both SigNH and non-SigNH. From these, 97.5% (348 of 357) showed 2 variants coexpression and 2.5% (9 of 357) showed 3 variants coexpression. In conclusion, the recent study can show the mutation patterns and risks associated with significant neonatal hyperbilirubinemia in the three ethnic groups of Malaysia. Out of 18 variants studied, 14 variants mutations of UGT1A1, G6PD, SLCO1B1 and α -thalassemia genes were detected. From these, promoter A(TA)nTAA, variant 211G>A of UGT1A1 gene and SLCO1B1 388G>A variants showed significance risk for SigNH group. In addition, co-expression of SLCO1B1 variant c.521T>C and UGT1A1 variant c.-3279T>G mutations showed significant difference in the frequency in SigNH and non-SigNH groups (p = 0.03).